2016
DOI: 10.1080/15532739.2016.1258352
|View full text |Cite
|
Sign up to set email alerts
|

Transgender and anxiety: A comparative study between transgender people and the general population

Abstract: Background:Anxiety disorders pose serious public health problems.The data available on anxiety disorders in the transgender population is limited by the small numbers, the lack of a matched controlled population and the selection of a nonhomogenous group of transgender people.Aims:The aims of the study were(1)To determine anxiety symptomatology (based on the HADS) in a non-treated transgender population and to compare them to a general population sample matched by age and gender;(2)To investigate the predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
121
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 61 publications
(29 reference statements)
4
121
1
7
Order By: Relevance
“…These high rates are consistent with recent studies on individuals who identify as transgender (Arcelus, Claes, Witcomb, Marshall, & Bouman, 2016; Bockting, Miner, Swinburne Romine, Hamilton, & Coleman, 2013; Dawson, Wymbs, Gidycz, Pride, & Figueroa, 2017), with our large and diverse data set underscoring the major needs of transgender individuals during college. Psychological factors like the expectation of rejection may lead students to feel unworthy and unsafe, leaving them more susceptible to MH challenges compared to their counterparts who classify as cisgender (Bouman et al, 2017; Denton, Rostosky, & Danner, 2014). Notably, these high rates of diagnoses might reflect greater service utilization use among sexual minorities (Kerr et al, 2013; Oswalt & Wyatt, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These high rates are consistent with recent studies on individuals who identify as transgender (Arcelus, Claes, Witcomb, Marshall, & Bouman, 2016; Bockting, Miner, Swinburne Romine, Hamilton, & Coleman, 2013; Dawson, Wymbs, Gidycz, Pride, & Figueroa, 2017), with our large and diverse data set underscoring the major needs of transgender individuals during college. Psychological factors like the expectation of rejection may lead students to feel unworthy and unsafe, leaving them more susceptible to MH challenges compared to their counterparts who classify as cisgender (Bouman et al, 2017; Denton, Rostosky, & Danner, 2014). Notably, these high rates of diagnoses might reflect greater service utilization use among sexual minorities (Kerr et al, 2013; Oswalt & Wyatt, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Transgender people experience incongruence between their gender assigned at birth [determined from their sex characteristics (i.e., genitals)] and the gender they identify with. Transgender men are assigned female at birth but identify as male, while transgender women are assigned male at birth but identify as female (Arcelus & Bouman, ; Bouman et al ., ). Cisgender people (non‐transgender) do not experience such incongruence.…”
Section: Introductionmentioning
confidence: 97%
“…Factors associated with, and found to mediate, eating disorder psychopathology in the cisgender population may be particularly pertinent among transgender people. This is because research has consistently shown treatment seeking transgender people to report high levels of mental health problems, such as anxiety and depression (e.g., Arcelus, Claes, Witcomb, Marshall, & Bouman, ; Bouman et al ., ; Bouman, Davey, Meyer, Witcomb, & Arcelus, ; Dhejne, Van Vlerken, Heylens, & Arcelus, ; Millet, Longworth, & Arcelus, ), perfectionism (Khoosal et al ., ), and interpersonal problems (Davey, Bouman, Meyer, & Arcelus, ) in comparison to cisgender people. Therefore, these factors may be important when exploring risk factors for eating disorder psychopathology within the transgender population.…”
Section: Introductionmentioning
confidence: 99%
“…Minority stress theory proposes that experiencing prejudice and discrimination related to stigma associated with holding a marginalized identity has a negative impact on health (Hendricks & Testa, 2012; Meyer, 2003). As a likely consequence to minority stress experienced as a result of stigma associated with being transgender, studies of mental health among transgender individuals, including youth, consistently show elevated rates of suicidality, anxiety, and depression (Bouman et al, 2017; Colizzi, Costa, & Todarello, 2014; Connolly, Zervos, Barone, Johnson, & Joseph, 2016; Millet, Longworth, & Arcelus, 2017; Perez-Brumer, Hatzenbuehler, Oldenburg, & Bockting, 2015; Reisner et al, 2015; Tebbe & Moradi, 2016; Warren, Bryant Smalley, & Nikki Barefoot, 2016). Mental and physical health care professionals have begun to see a substantial rise in referrals for gender nonconforming youth (Malpas, 2011; Meyer, 2012; Alegria, 2011; Olson-Kennedy, 2016).…”
mentioning
confidence: 99%